Pengaruh Media Prezi terhadap Minat Belajar Siswa Kelas IX Mata Pelajaran Pendidikan Agama Islam di MTs Fathus Salafi: The Influence of Prezi Media on the Learning Interest of Grade IX Students in Islamic Religious Education Subjects at MTs Fathus Salafi - Yuliana, Dyan; Hardian, Hardian (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The results of observations conducted by researchers at MTs Fathus Salafi found that there were obstacles related to the use of learning media, namely that the school had not used any learning media, especially in Islamic Religious Education subjects. Learning media is essential to stimulate students' enthusiasm and encourage them to be more interested in learning activities. This study aims to determine the effect of Prezi media on the learning interest of class IX students in Islamic Religious Education subjects at MTs Fathus Salafi. This type of research is a quantitative research experimental method with a quasi-experimental design in the form of a nonequivalent control group design. The respondents were class IX students at MTs Fathus Salafi. Primary data were collected using a questionnaire, analyzed for validity and reliability, and then tested with the t-test. The study results obtained tcount = 0.553 <ttable = 1.669 with Sig. (2-tailed) = 0.582> 0.05, so Ha was rejected, and H0 was accepted. Thus, it can be concluded that the use of Prezi media has no influence on the learning interest of grade IX students in Islamic Religious Education subjects at MTs Fathus Salafi in the 2020/2021 Academic Year.